Answer:
$3599.57
Step-by-step explanation:
Using the compound interest formula Accrued Amount = P (1 + r)^t
where Accrued amount is to be determined
P = principal; $3200
r = 4% = 0.04
t = number of years = 3
Therefore
Accrued amount = 3200 (1 + 0.04)^3
= 3200 x 1.04^3
= 3200 x 1.1249
= 3599.57
The total amount after 3 years is $3599.57
Answer:
n < -10
Step-by-step explanation:
The value of the number can be equal to or less than -3
(f∘g)(x) is equivalent to f(g(x)). We solve this problem just as we solve f(x). But since it asks us to find out f(g(x)), in f(x), each time we encounter x, we replace it with g(x).
In the above problem, f(x)=x+3.
Therefore, f(g(x))=g(x)+3.
⇒(f∘g)(x)=2x−7+3
⇒(f∘g)(x)=2x−4
Basically, write the g(x) equation where you see the x in the f(x) equation.
f∘g(x)=(g(x))+3 Replace g(x) with the equation
f∘g(x)=(2x−7)+3
f∘g(x)=2x−7+3 we just took away the parentheses
f∘g(x)=2x−4 Because the −7+3=4
This is it
g∘f(x) would be the other way around
g∘f(x)=2(x+3)−7
now you have to multiply what is inside parentheses by 2 because thats whats directly in front of them.
g∘f(x)=2x+6−7
Next, +6−7=−1
g∘f(x)=2x−1
Its a lts easier than you think!
Hope this helped